Internet interventions for depression: new developments - Schröder, Johanna (Dialogues Clin Neurosci, 2016)
A wide range of Internet interventions, mostly grounded in methods of cognitive behavioral therapy, have been developed and tested for several mental disorders. The evidence to date shows that these interventions are effective in reducing symptoms of depression. Metaanalyses report small-to-medium effect sizes when Internet interventions are delivered as stand-alone self-help interventions (d=0.25-0.36), and medium-to-large effect sizes when delivered as therapist-guided interventions (d=0.58-0.78), both compared with usual care. Only a minority of people suffering from depression receive adequate treatment, and Internet interventions might help bridge the large treatment gap. This review summarizes the current body of evidence and highlights pros and cons of Internet interventions. It also outlines how they could be implemented in mental health care systems and points out unresolved questions, as well as future directions, in this research field.